Therapeutic potential of Curcuma longa against monkeypox: antioxidant, anti-inflammatory, and computational insights - Farouk Boudou; Amal Belakredar; Ahcen Keziz; Linda Aissani; Huda Alsaeedi; David Cronu; Mikhael Bechelany; Mikhael Bechelany; Ahmed Barhoum (Frontiers in Chemistry)
BackgroundMonkeypox (Mpox) is a re-emerging zoonotic disease with limited therapeutic options, necessitating the exploration of novel antiviral agents. Curcuma longa (turmeric) is a widely used medicinal plant known for its antioxidant and anti-inflammatory properties, primarily attributed to its bioactive curcuminoids.AimThis study aimed to evaluate the therapeutic potential of C. longa aqueous extract (CAE) against monkeypox through phytochemical characterization, biological assays, and computational analyses.MethodologyPhytochemical analysis, including HPLC, identified key Curcumin, Bisdemethoxycurcumin, Demethoxycurcumin, Tetrahydrocurcumin, Curcuminol, and Ar-curcumene. The DPPH assay and total antioxidant capacity (TAC) were employed to assess antioxidant activity. Anti-inflammatory effects were determined by measuring the inhibition of heat-induced protein denaturation. Molecular docking and molecular dynamics (MD) simulations were performed to evaluate the interactions between curcuminoids and monkeypox virus proteins.ResultsThe aqueous extract of C. longa was prepared via decoction, yielding 7.80% ± 0.81% extract with curcumin as the predominant compound (36.33%). The CAE exhibited strong antioxidant activity with a TAC of 36.55 ± 0.01 µg GAE/g d.w., an IC50 of 0.77 ± 0.04 mg/mL in the DPPH assay, andan EC50 of FRAP of 3.46 ± 0.11 mg/mL. Anti-inflammatory analysis showed 78.88 ± 0.53%inhibition for egg albumin and 90.51 ± 0.29%for BSA. Molecular docking identified demethoxycurcumin (DMC) as the most potent compound, with binding affinities of −8.42 kcal/mol (4QVO), −7.61 kcal/mol (8CEQ), and −7.88 kcal/mol (8QRV). MD simulations confirmed the stability of DMC complexes, with the 4QVO-DMC interaction being the most stable, showing RMSD fluctuations within a range of 0.2–0.6 nm, with an average fluctuation of 0.4 nm, and consistent compactness with Rg values remaining between 1.8 and 2.0 nm, with a fluctuation of only 0.2 nm over 100 ns.DiscussionThe results demonstrate the multifunctional therapeutic potential of C. longa, driven by its potent antioxidant and anti-inflammatory properties. The computational findings suggest that curcuminoids, particularly demethoxycurcumin, could serve as promising antiviral agents against monkeypox. These findings pave the way for further preclinical studies to validate the antiviral efficacy of C. longa bioactives and their potential applications in combating viral infections.